For class eight: all formula
āĻŦীāĻāĻāĻŖিāĻ¤েāĻ° āĻ¸ূāĻ¤্āĻ°āĻ¸āĻŽূāĻšঃ
• (a + b) 2= a 2 + 2ab + b 2
• (a + b) 2= (a – b) 2 + 4ab
• (a – b) 2 = a 2 – 2ab + b 2
•(a – b) 2 = (a + b) 2 – 4ab
• a 2 + b 2 = (a + b) 2 – 2ab
• a2 + b2 = (a – b) 2 + 2ab
• a 2 – b 2 = (a + b) (a – b)
• 2 (a 2 +b 2) = (a + b) 2 + (a – b) 2
• (a + b + c) 2 = (a 2 + b 2 + c 2) + 2 (ab + bc + ca)
• (a 2 + b 2 + c 2) = (a + b + c) 2 – 2(ab + bc + ca)
• 2 (ab + bc + ca) = (a + b + c) 2 – (a2 + b2 + c2)
• (a + b)³= a³ + 3a2b + 3ab2 + b³
• (a + b) ³= a³ + b³ + 3ab (a + b)
• (a – b) ³= a³ – 3a2b + 3ab2 – b3
• (a – b) ³= a³ – b³ – 3ab (a – b)
• a³ + b³ = (a + b) (a2 – ab + b2)
• a³ + b³ = (a + b) ³– 3ab (a + b)
• a³ – b³ = (a – b) (a2 + ab + b2)
• a³ – b³ = (a – b) ³+ 3ab (a – b)
• (a + b + c) ³= a³ + b³ + c³ + 3 (a + b) (b + c) (c + a)
• a³ + b³+ c³ – 3abc = (a + b + c) (a2 + b2 + c2– ab – bc – ca)
• a3 + b3 + c3 – 3abc = (a + b + c) { (a – b)2 + (b – c) 2+ (c – a) 2}
• 4ab = (a + b) 2– (a – b) 2
• (x + a) (x + b) = x2 + (a + b) x + ab
• (x + a) (x – b) = x2 + (a – b) x – ab
• (x – a) (x + b) = x2 + (b – a) x – ab
• (x – a) (x – b) = x2 – (a + b) x + ab
• (x + p) (x + q) (x + r) = x³ + (p + q + r) x2 + (pq + qr + rp) x +pqr
• bc (b – c) + ca (c – a) + ab (a – b) = – (b – c) (c – a) (a – b)
• a2(b – c) + b2 (c – a) + c2 (a – b) = – (b – c) (c – a) (a – b)
• a(b2 – c2) + b (c2 – a2) + c (a2 – b2) = (b – c) (c – a) (a – b)
• a³ (b – c) + b³ (c – a) + c³ (a – b) = – (b – c) (c – a) (a – b) (a + b + c)
• (ab + bc + ca) (a + b + c) – abc = (a + b) (b + c) (c + a)
• (b + c) (c + a) (a + b) + abc = (a + b +c) (ab + bc + ca)
Comments